How did it happen: Exploring 25 years of research on founder succession - Ming-Chang Cheng; Quynh-Nhu Tran-Pham (Cogent Business & Management, 2022)
We choose to examine founder succession as a benchmark of the entrepreneurial transition phenomenon and employ bibliometric analyses of 151 articles on founder succession research published in peer-reviewed journals from 1997 to 2021 to provide a systematic assessment of the existing literature. Keyword co-occurrence analyses map out important topics and hot trends in this research. Co-authorship network analyses clarify the community of renowned scholars working on this literature stream and their co-authorship preferences. Their citation patterns and various bibliometric parameters clearly exhibit the emergence of founder succession as a potential literature. Finally, discussion of findings and recommendations for future research are discussed.
Keywords: 650; start-ups; bibliometrics; founder departure; founder succession; individual level entrepreneurship; Life Cycle theory; new ventures; organizational level entrepreneurship; Resource Dependence theory; the entrepreneurial transition